Pheochromocytomas and paragangliomas in North African population: a single-tertiary center experience - Imane Rami; Fatim Zahra Bentebbaa; Imane Assarrar; Rania El Amel; Siham Rouf; Hanane Latrech (Arterial Hypertension)
Introduction: Pheochromocytomas (PCC) and Paragangliomas (PGL) are rare endocrine tumors. This study aimed to describe our experience with these two entities in a particular population. Methods: We identified patients with positive histopathological confirmations of PCC and PGL who were treated at a tertiary center hospital between 2014 and 2023. The results were analyzed for clinical presentations, treatment, and long-term outcomes. Results: A total of 35 cases (30 PCC, 5 PGL) were identified over 9 years. The mean age of our patients was 47 ±18.1 years with a M/F sex ratio of 0.6. Blood hypertension was present in 58.8% of cases and diabetes in 47% of cases. In 35.3% of the patients, PCC was discovered during the investigation of an adrenal incidentaloma, 8.8% in the context of hereditary diseases, and 55.9% following symptoms. All patients had high levels of urinary or plasma metanephrines. Imaging was performed in all patients revealing a unilateral tumor in 90% of cases and bilateral tumors in 10%. At the postoperative follow-up, all hypertensive patients achieved good blood pressure control, resulting in a reduction in antihypertensive treatment. In addition, glycemic control improved significantly in the remaining cases. Long-term follow-up included 3 deaths, only one recurrence, and no metastases with a mean follow-up of 4.6 ±1.3 years. Conclusion: The present study confirms that the clinical presentation of pheochromocytoma is variable and non-specific. Usually, the tumor is discovered incidentally. Although pheochromocytoma is a rare tumor, appropriate evaluation, preoperative preparation, genetic testing and complete surgical resection are crucial for its management